PERAN KOMNAS HAM DALAM SENGKETA TANAH ULAYAT REMPANG ECO CITY - Alya Rahmadani; Kelvina Marsya Indiharsari Widodo; Rossela Arneta Putri; Salsabila Fitriah Puteri (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
The abundance of natural resources in Indonesia has led to various conflicts involving land rights inherited from indigenous peoples. The conflict escalates when it is related to large-scale development projects involving various parties, one of which is the Rempang Eco City project which is a National Strategic Project (PSN), which contains pros and cons between the Malay indigenous community on Rempang Island and the Batam Business Agency (BP). In dealing with this kind of conflict, the National Human Rights Commission (Komnas HAM) has a significant role because it is left as a supervisor and mediator in conflicts related to human rights violations, including land rights for indigenous peoples. This study uses a qualitative method to determine the role of Komnas HAM as a mediator in the land rights conflict for indigenous peoples in the case of Rempang Island. The study will use the theory of political strategy as an analytical tool in the case study that the researcher raised. The results found that even though mediation by Komnas HAM had been carried out, BP Batam remained adamant about continuing this project. There are obstacles for Komnas HAM because it was proposed as a mediator and until now it has not obtained satisfactory results to defend the rights of indigenous peoples. This comes back to the role of the government which should be more assertive by not prioritizing the interests of investors, but also considering the rights of local communities.